If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 2m + -1(9) Multiply -1 * 9 15 = 2m + -9 Reorder the terms: 15 = -9 + 2m Solving 15 = -9 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 15 + -2m = -9 + 2m + -2m Combine like terms: 2m + -2m = 0 15 + -2m = -9 + 0 15 + -2m = -9 Add '-15' to each side of the equation. 15 + -15 + -2m = -9 + -15 Combine like terms: 15 + -15 = 0 0 + -2m = -9 + -15 -2m = -9 + -15 Combine like terms: -9 + -15 = -24 -2m = -24 Divide each side by '-2'. m = 12 Simplifying m = 12
| 2.8=v/4 | | 5m^3/m^3 | | 7(x+4)=7x | | 8x-45=6x+15 | | -7=y-11 | | -8x-3+5x+4= | | 4x-2=1+3x | | 5x+1=5+6x | | x/4-6=2 | | Y+7/2+Y-17/9 | | 1/25-9z^3 | | 3(-4-6y)+4(-1-5w)=50 | | 10+a/3=-1 | | 20x-10+24-4x-15x-5=-3 | | 32x-16y=98 | | b/-3=-6 | | 5x-1=5+6x | | X^2+13xy+12y^2= | | -2(r-1)=-2 | | (4-5x)/6=7 | | 16/15X=48 | | -7x+x-75=75 | | -10x+5=-9x-9 | | 8/3x+1/3x=4x+30/3+7/3x | | 1/2(6x-3)=-24 | | -3y-8=5y+12 | | 3x^2-42x+120=0 | | 11/6X=44 | | 16=x/5+5 | | -24b-16+25b-6=0 | | -4u^2+9u-3= | | 12-7x=-44 |